Nursing experiences in caring for older adults with COVID-19: according to the Joyce-Travelbee model - Ibarra-González, Cinthya Patricia; Ramírez-Hernández , Sandra Angelica; Ramos-Luna , San Juana de Jesús; García-Vázquez, María del Refugio; Carbajal-Mata , Flor Esthela; Velázquez, Mireya (Horizonte Sanitario, 2025)
Objective: It was to explore the experiences of the Nursing professional in caring for older adults hospitalized with COVID-19, based on the five phases of Joyce Travelbee's person-person model.Materials and Methods: Exploratory with a qualitative approach of a descriptive and observational nature, from a phenomenological perspective, in nursing professionals who work in health institutions in Mexico City, obtaining a sample of 18 participants. A semi-structured interview was applied under the guidelines of the General Health Law.Results: Five categories and thirteen subcategories were identified, which were in the five phases of Joyce Travelbee's person-person model. The categories followed by their subcategories were: communication (verbal, non-verbal, video calls and letter reading), nursing care (accompaniment, maintenance of skin integrity and mobility and posture), knowledge (physical and mental impairment due to COVID-19), emotions (positive and negative) and experiences (learning and skills).Conclusions: The Travelbee Model can be applied to explain the experiences of the relationship between the nurse and the patient, since from this the need to link to this binomial found a meaning that is useful to improve the quality of care is observed. to this highly vulnerable population. Keywords: Experiences; Nursing; Older adults; Hospitalization; COVID-19.